Encapsulation of Soursop (Annona muricata Linn.) Leaf Tea Extract Using Natural Mucilage - Melanie Cornelia; Kam Natania; Herry Cahyana; Edison Sutiyono (Reaktor, 2019)
The bioactively rich soursop leaf extract can be encapsulated inside several natural coating materials. The extract of soursop leaf has been found to contain many bioactive compounds such as various phenolic compounds that are beneficial for anticancer, antidiabetic and many other health benefits. However due to the sensitive nature of the bioactive molecules, encapsulation procedure was applied to prolong the activity of the biomolecules. Capsule materials used in this experiment were obtained from natural extract of Okra mucilage, Aloe vera mucilage and Maltodextrin-WPI mixture to protect the unstable bioactive compounds. Homogenation time using ultrasonication and Core to Coating ratio was differed to observe the optimum encapsulation process. The encapsulation efficiency, release factor ability, size distribution and its correlation with bioactive stability are observed using Total Phenolic methods and Antioxidant Activity before and after encapsulation. Aloe vera gave best encapsulation efficiency (88-91%) while microcapsule made with Okra gave the best antioxidant activity (DPPH IC50 633-710ppm), and maltodextrin-WPI gave best powder recovery (yield 70-73%). Keywords: aloe mucilage, antioxidant activity,  encapsulation, okra mucilage, soursop tea extract